Effects of ageing population and regulatory performance in moderating the debt-growth relationship in the upper-middle-income economies / Nur Hayati Abd Rahman - Abd Rahman, Nur Hayati (2020)
The upper-middle-income economies (UMIE) must strategize and boost their economic growth if they want to move away from the middle-income trap position. It is possible if the economies inject a massive amount of funds for their economic growth and development. However, previous statistics show that the UMIE were experiencing an economic slowdown due to a decline in the level of investments, a rise in the number of ageing population as well as a weak regulatory performance. Due to these challenges, it is getting harder for the UMIE to grow further if they do not have additional sources of funds. Raising or introducing new taxes is not a solution since it creates a distortionary effect to the economy. Instead, the government might opt for external borrowings even though it is highly vulnerable to the economic growth. Therefore, this thesis aims to examine how the UMIE can grow further even when they are facing these four issues. The scope of this research covers 32 countries in the UMIE from the year 1990 to 2018 as these countries had the possibility to get stuck in the middle-income trap position. In removing the elements of the business cycle, all data were divided into six periods, based on the non-overlapping five-year averages. The system Generalized Method of Moments (henceforth, GMM) was employed as an estimation method since it is suitable for data with a small time but large cross-sections. Besides, it has the capabilities to solve the endogeneity problem in the debt-growth model. The findings show that the UMIE can drive their economies by utilizing their gross savings and attracting more domestic and foreign investments. Even when the investment level is declining, the growth is still possible if the savings are channelled to the human capital development. Apart from the three, public debt is also essential to achieve a higher economic growth, but with a condition that the ratio of debt to GDP is not exceeding 70 per cent. The growth will start to diminish when the debt to GDP ratio exceeds 70 per cent. In addition, it is a surprise to find that the debt helps the economy to grow even when the countries are having large number of ageing population, probably due to the shift of the economic structure towards capital and technology intensive. Similarly, a high public debt is expected to enhance the economic growth of the UMIE when the regulatory performance is improved. These findings lead to few policy implications, which are explained in the last chapter of this thesis.